Análise da estabilidade global em edifício de concreto armado utilizando os parâmetros de instabilidade gamaz e FAVt no software TQS - Landucci, Gabriel Franco (2024)
Urban centers are becoming denser due to several factors, such as job offer and access to resources and services, promoting the vertical growth of buildings and increasing the concern of structural designers. The increase in buildings with multiple floors, subject to horizontal forces such as wind, requires verification of global stability to ensure user safety, as established by NBR 6118 (ABNT, 2023). When studying global stability, internal aspects are considered, such as the composition of the structural elements, and external aspects, such as the loads acting on the structure, in order to determine displacements, global stiffness and identification of the elements responsible for stability. First and second order theories are applied, together with structure approximations, to simplify and make the results viable. With the advancement of technology, the use of structural analysis software becomes essential for an accurate assessment of the real structure. This work aims to analyze the influence of height on the global stability of a multi-story reinforced concrete building using the stability parameters from NBR 6118 and the FAVt parameter exclusive to the TQS software. The parameters and FAVt evaluate global stability, with FAVt considering the horizontal displacement resulting from vertical and horizontal loads and only considering the horizontal displacements caused by horizontal efforts. To conduct the study, a fictitious structure was selected and several modelings were carried out in the CAD/TQS software, varying the geometry and height. These modifications, total height in the structures result in an increase in their slenderness, and an increase in second order efforts, that is, they exhibited higher values of instability.